Synthesis, Characterization of Some Novel Benzimidazole Derivatives of 1-Bromo-2,4-dinitrobenzene and Their Antifungal Activities - Abbas Ahmadi; Babak Nahri-Niknafs (E-Journal of Chemistry)
Six novel benzimidazole derivatives, 5-nitro-2-phenyl -1-ethyl benzimidazol (5), 2- (p-bromophenyl)- 5-nitro- 1-ethyl benzimidazol (6), 2- (p-bromophenyl-5-nitro-1–cyclopentyl benzimidazol (7), 2- (p-bromophenyl) -5-nitro-1-cyclopentyl benzimidazol (8), 5-amino-2-(p-bromophenyl)-1-ethylbenzimidazol (9) and 5-amino-2-(p-bromophenyl)-1-cyclopentyl benzimidazol (10) were synthesized. The structures of all the synthesized compounds were elucidated by using elemental analysis and different spectroscopic techniques (IR, NMR and mass spectroscopy). Some of these compounds showed potential antifungal activities. The biological activity of these compounds as fungicides was tested against Candida albicans, patient isolate Candida glabrata and Candida krusei. The biological activity of four compounds was found to be comparable to that of the commercially available fungicides with a minimum inhibitory concentration of 12.5 µg/mL.